OPTIMIZATION OF PROPPANT VOLUME ALLOCATION IN HYDRAULIC FRACTURING FOR MULTILAYER OIL RESERVOIR - Nico Calvin Alexandro, Nikolas
Hydraulic fracturing has been around in the oil and gas industry since 1949, but it is more popular than ever now. Hydraulic fracturing has also been applied for multilayer reservoirs. But has it been done optimally in multilayer reservoir? In this study, the writer intend to optimize the allocation of a provided proppant volume for each layer in multilayer reservoir by finding the maximum value of total productivity index for all the layers. The variables that will be considered in this study are layer thickness and permeability. Each layers will have different permeability and/or thickness, where those layer properties will affect the optimum fracture half-length and width. This study is also validated by using CMG software to compare oil cummulative production for cases where the proppant volume allocation has not been optimized and for the one where it has been.